A recepção de Theodor Adorno no universo intelectual e acadêmico brasileiro (1950-2015) - Saiz, Gustavo dos Santos Rey (2017)
This dissertation aims to present the trajectory of the Brazilian reception of the German philosopher Theodor Adorno. Linked to the Institute of Social Research - from which would emerge the "Frankfurt School" - Adorno begins to receive attention from Brazilian intellectuals between the decades of 1950 and 1960. Since then, researchers from different areas have looked out to the work of this author, creating what we called, following Pierre Bourdieu, an academic field. This trajectory involved distinct readings, appropriations and definitions about the author, built and criticized over time. This dissertation intends to analyze this processes locating them in it's different historical moments